SIKLUS KONVERSI KAS, PROFITABILITAS DAN NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Elfita Rahmantika; Agung Juliarto (Diponegoro Journal of Accounting, 2020)
This study aims to determine about cash conversion cycle, profitability and firm value in manufacturing firms that have been listed on the IDX. This study uses two research models, cash conversion cycle as an independent variable and firm profitability as a dependent variable in the first model, and firm profitability as an independent variable and firm value as a dependent variable in the second model. This quantitative research is using a secondary dataset in the form of annual reports taken from the idx.co.id site. There are 82 samples that fit into the criteria out of 147 populations of manufacturing firms that have been listed on the IDX during 2014-2016. This study used a simple linear regression analysis and SPSS 21.The results showed that the cash conversion cycle has a significant negative effect on firm profitability, and the firm profitability has a significant positive effect on firm value.